3D kinematic of lower limbs in freestyle cross-country skiing (XCS) technique during WC (Dobbiaco 2012) and WCHS (Fiemme 2013) - Canclini, A.; Canclini, A.; Pozzo, R.; Baroni, G. (Science and Skiing VII, 2018)
The new freestyle (FT) in XCS was formally introduced in 1985 in specialized races in addition to the original races in classical technique. In the last three decades, the freestyle has considerably developed due to several factors: new equipment and materials, better preparation of ski tracks, and improvement in the training methodology and in the skiers` techniques depending on terrain and drag forces (Lindinger et al., 2007). A free-skiing race challenges the athletes to master a wide range of speeds and slopes, and to adapt their technique accordingly. Thus, skiers possess different skiing techniques and continuously change among them during a race. The skating technique has five predominant subtechniques, known as gears (G1-5) as suggested by Nilsson et al. 2004 (G2, G3, and G4 replace the old names V1-V2 and V2alternate). In the 1990s, several studies were conducted in an attempt to describe the most relevant aspects of XCS freestyle, but the kinematic information was generally limited in the velocity range. More recently, Kvamme et al. (2005), Smith et al. (2007), Lindinger et al. (2010), StOggl et al. (2010), and Andersson et al. (2010) compared biomechanical characteristics of the main skating techniques. The purpose of this work was to collect and to analyze the 3D kinematics of the main gears (G2, G3, G4) in freestyle XCS performed by elite skiers engaged in recent top races. We focused on the lower-limb posture, and we measured the ski orientation angle and edging angle. Results were also compared to the mathematical model proposed by Driessel (2004).